(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Examining the effects on the mental health of women who have been victims of domestic abuse is the focus of the current research. In India, any kind of violence suffered by a person’s natural family members is considered domestic violence. However, the most common form of domestic violence is male-on-female assault. Among women aged 15–49, the absolute prevalence of domestic abuse was 33.5% and sexual violence 8.5% in a 2005 National Family and Health Survey. With two kinds of areas (rural and urban). Levels of education, years of age were considered. For this study, we will recruit 200 female victims of domestic abuse. Of these, 100 will come from rural areas, and 50 will be from metropolitan areas. Of these 100, 50 will have bachelor’s degrees or less, and 25 will have master’s degrees or more. Researchers in Gujarati surveyed both employed and unemployed women using the Mental Health Scale developed by Dr. D.J. Bhatt and Kumari G.R. Gida. Write the research study report in clear and concise language so that readers may assess its strength and sufficiency. The mental health of women who have been victims of domestic abuse has not been significantly affected.